The Effect Of Reinforced-Epoxy Coating On The Bending Modulus Of Micro-Cantilever Using Phase-Shift Shadow Moiré. - Lim, Jiunn Hsuh (2012)

(untitled)
Applying an accurate bending modulus value of the material is important in the design and analysis of the reinforced-epoxy coated PET cantilevers. This is because the accurate bending modulus value is important in evaluating the effect of the various coatings onto the micro-cantilever. This research is aimed at applying the phase-shift shadow moiré method (PSSM) for the deflection measurement of reinforced-epoxy coated PET micro-cantilevers in order to determine the bending modulus of the micro-cantilever material. The PSSM was initially developed to measure the deflection of a miniaturized copper cantilever and the feasibility of the method was studied to measure micro-deflection. The PSSM was then modified and improved using image processing techniques to enhance the poor visibility moiré fringes before applying it to measure the deflection of a silicon micro-cantilever. The silicon micro-cantilever specimen was fabricated using surface micro-machining technique. The improved PSSM method was successfully applied to process poor visibility fringe patterns and deflection data was extracted. A study on the effect of different coating materials in the reinforced-epoxy coated PET micro-cantilever was then carried out. The samples were fabricated by applying the aluminum-epoxy and graphite-epoxy coatings on PET sheets through a mold. The micro-cantilevers specimens were then released by cutting the PET with coating according to the patterns of the mold. The various types of the reinforced-epoxy coatings were found xviii to affect the bending modulus of the coated PET micro-cantilevers. The bending modulus increased as the percentages of the aluminum and graphite reinforcement in the epoxy increased. The study of the effect of the coating materials were extended by using the finite element analysis (FEA). The bending modulus values of the various types of coating materials determined from experimental work were applied as the input parameter and the thickness of the coatings were altered. The investigation from the FEA suggested that the optimum thickness of reinforcedepoxy coating is about 180 μm based on the increment of the stiffness. The research work was focused on the specimen preparation and improvement of the PSSM method with image enhancement technique, as well as the study of the effect of the coating on PET cantilever. The research shows that the improved PSSM method is capable of measuring the micro-deflection with minimum error and the bending modulus of the micro-cantilever can be altered by using different coating materials. Without changing the major dimensions of the micro-cantilever, the bending modulus of the composite cantilever material can be varied and therefore microcantilevers with different sensitivities can be produced.